Evaluation of the efficacy of dentin hypersensitivity treatments - a systematic review and follow-up analysis - Marto, CM (2019)
OBJECTIVES: To compare the treatments used to treat dentin hypersensitivity (DH), based on its efficacy and effect duration. METHODS: Medline/PubMed, Cochrane Library, EMBASE, and ClinicalTrials were searched for articles published between January 1st , 2008 and November 14th , 2018, in English, Portuguese or Spanish, reporting clinical trials, completed and with results. This systematic review protocol was registered in PROSPERO, number CRD42019121986. RESULTS: 74 randomized clinical trials were included in the systematic review, reporting patients from 16 to 65 years old, with a clinical diagnosis of DH, that evaluate the efficacy of a desensitizing product, compared to pre-treatment, used the evaporative method stimulation and the visual analogue scale. These studies evaluated 5366 patients and at least 9167 teeth. Seven follow-up periods were considered corresponding to an immediate, medium or long-time effect. 66 studies were included in the quantitative synthesis. Glutaraldehyde with HEMA, glass ionomer cements and Laser present significant immediate (until 7 days) DH reduction. Medium term (until 1 month) reduction was observed in stannous fluoride, glutaraldehyde with HEMA, hydroxyapatite, glass ionomer cements and Laser groups. Finally, long term significant reduction was seen at potassium nitrate, arginine, glutaraldehyde with HEMA, hydroxyapatite, adhesive systems, glass ionomer cements, and LASER. CONCLUSIONS: All active ingredients show efficacy in DH reduction in different follow-up times. Only in-office treatments are effective in immediate DH reduction, maintaining its efficacy over time. For long time effects, at home treatments can also be used. More standardized evaluation protocols should be implemented to increase the robustly of the results.